Occupant exposure and ventilation conditions in Chinese residential kitchens: Site survey and measurement for an old residential community in Shanghai. (September 2020) - Zeng, Lingjie; Du, Bowen; Lv, Lipeng; Gao, Jun; Zhang, Chengquan; Tong, Leqi; Liu, Guodong
Abstract: Chinese residents often use range hoods to exhaust cooking oil fumes (COF) and at the same time open inner/outer doors and windows for natural air supplement. Factors such as the layout of kitchens, the exhaust efficiency of range hoods, and the effect of natural air supplement, directly determine transmission characteristics of COF, which in turn affect the capture efficiency of range hoods and the COF exposure of residents. This study carried out a survey on the ventilation conditions in residential kitchens and conducted measurement of residents' COF exposure. In an old residential community of Shanghai, we measured the three-dimensional size of kitchens, the areas and positions of doors and windows and the exhaust rate of range hoods of 30 residential kitchens. 7 households were randomly selected to monitor 24-h PM2.5 concentration around stoves in kitchens. Meanwhile, one volunteer from each of the 30 households participated in personal PM2.5 monitoring using wearable sensors. To quantify the occupant exposure during cooking, two indexes including the exposure contribution rate and additional exposure concentration were introduced. The results showed that the ventilation conditions in these kitchens were generally poor and considerably different from each other. Meanwhile, the concentration dynamics of PM2.5 during cooking showed short-term (about 10–20 min) and high-dose (the peak concentration reached 800–1000 μg/m 3 ) characteristics compared with that in other periods. Highlights: Defining exposure contribution rate and additional exposure concentration to quantify PM exposures of volunteers. The concentration dynamics of PM2.5 during cooking has characteristic of short-term and high-dose. The ventilation conditions in old Chinese residential kitchens are generally poor and considerably different from each other.